The Influence of Servant Leader Leadership Style and Culture Value with the Intervening Variable of Work Motivation on the Performance of the Head of the Work Unit at PNM Magelang Branch - Santosa, Budi; Safaria, Siti (Formosa Journal of Sustainable Research, 2024)
The purpose of the study is to analyze the effect of servant leader leadership style on motivation, culture value on motivation, servant leader leadership style on performance, culture value on performance, motivation on performance, servant leader leadership style to performance through motivation, culture value through to performance through motivation of the head of PNM Magelang Branch. Using quantitative research with population and samples, saturated sampling are PNM employees who serve as heads units at the Magelang Branch, 64 employees. Using SEM, Smart Pls version 4 servant leader have no significant effect on motivation. Culture value have a significant effect on motivation. Servant leadership have no significant effect on performance, Culture value have a significant effect on performance, Culture value have a significant effect on performance through motivation as intervening variable, Servant leader have no significant effect on performance through motivation as intervening variable. work unit PNM Magelang Branch